Peran Kelembagaan Lokal Dalam Upaya Pelestarian Cagar Alam Faruhumpenai Kabupaten Luwu Timur - asikin, muchtar; Sulistyaowati, Novi; Kadir, Abd; Wahyullah; Kultsum, Ummu (Jurnal Hutan dan Masyarakat, 2024)
ABSTRACT. This research aims to explore the role of local institutions in maintaining and protecting the Faruhumpenai Nature Reserve forest area. The aim is to identify the challenges and obstacles faced by local institutions in efforts to preserve these forest areas. Apart from that, this research will also evaluate the efforts made by each institution to preserve the Faruhumpenai Nature Reserve forest area. Data was collected around the Faruhumpenai Nature Reserve Area which is located in Mangkutana District, East Luwu Regency, South Sulawesi Province. The research was conducted using a qualitative approach for primary and secondary data. The method used is a case study method with a deliberate sample selection approach. Primary data was obtained through interviews with leaders such as chairman, secretary and important members of local institutions, with a total of 25 respondents. Hasil penelitian menunjukkan bahwa peran lembaga lokal adalah untuk mengadakan program sosialisasi dan melakukan penanaman pohon di kawasan Cagar Alam Faruhumpenai, bertindak sebagai mitra pemerintah dalam upaya pelestarian lingkungan. Meskipun demikian, lembaga lokal menghadapi berbagai kendala dan hambatan dalam menjaga kelestarian alam di kawasan hutan Cagar Alam Faruhumpenai, termasuk kurangnya kapasitas sumber daya manusia, seringnya terjadi perbedaan pendapat, kurangnya pengetahuan tentang teknologi informasi dalam era digital, serta adanya tantangan egoisme dan kurangnya dukungan finansial. Namun, lembaga lokal telah melakukan upaya seperti sosialisasi tentang penanggulangan banjir dan tanah longsor, penanaman pohon di area tersebut, serta mengadakan kegiatan pembersihan dengan pengelolaan sampah dan sungai. Key words: local institutions, nature reserves, forest conservation